Pengaruh Pemberian Mulsa Chromolaena odorata (L.) Kings and Robins pada Kandungan Mineral P dan N Tanah Latosol dan Produktivitas Hijauan Jagung (Zea mays L.) - N R Kumalasari; L Abdullah; S Jayadi (Media Peternakan, 2005)
Corn is used as foodstuff and industrially utilized feed as a potential ingredient in animal ration. Green forage, baby corn and its cobs are used also as ruminants feed. Application of Chromolaena odorata on latosol as mulch material is expected to improve corn production by contributing organic nutrition. The objectives of this research were to recognize the effect of Chromolaena odorata on production and quality of green forage of high density corn, and to observe the contribution of phosphorous mineral from decomposition of Chromolaena odorata in the ground. This research was divided into two steps of experiment. The first experiment, consisted of two levels of treatments, i.e.: with and without Chromolaena odorata (12 ton/ha). The plants were fertilized with 60 kg K/ha and 225 kg N/ha. Plant was harvested at 40 days after planting. In the second experiment, corns were cultivated in the same area and the application of mulch (12 ton/ha) and P (60 kg/ha). Mulch increased significantly vertical height but there was no effect on production of green forage, mineral content in crop and uptake of P and N. In the second experiment, mulch addition improved vertical height of the crop, fresh and dry weight of green forage, content of P and N on the tissues of crop and also uptake of P and N between two treatments were not significant. Application of Chromolaena odorata mulch (2x12 ton/ha) was similar as the addition of P anorganic (60 kg/ha) in improving growth, production and quality of green forage of corn. In this research, the mulch improved the content of mineral P and N in the soil. Key words: mulch, Chromolaena odorata, mineral P, corn